2010
DOI: 10.1103/physrevlett.105.097206
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Chirality Decoupling in the One-Dimensional Heisenberg Spin Glass with Long-Range Power-Law Interactions

Abstract: We study the issue of the spin-chirality decoupling or coupling in the ordering of the Heisenberg spin glass by performing large-scale Monte Carlo simulations on a one-dimensional Heisenberg spin-glass model with a long-range power-law interaction up to large system sizes. We find that the spin-chirality decoupling occurs for an intermediate range of the power-law exponent. Implications to the corresponding d-dimensional short-range model are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…Again, the inset shows log-log fits assuming that the transition temperature, T CG in this case, is zero. The fit is satisfactory and indicates that we do not find a finite value for T CG at σ = 1, in contrast to the claim of Viet and Kawamura [20]. Figure 14 shows the data for χ SG .…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Again, the inset shows log-log fits assuming that the transition temperature, T CG in this case, is zero. The fit is satisfactory and indicates that we do not find a finite value for T CG at σ = 1, in contrast to the claim of Viet and Kawamura [20]. Figure 14 shows the data for χ SG .…”
Section: Resultsmentioning
confidence: 61%
“…It is known from the early work of Kotliar et al [3] that σ = 1 is the "lower critical" value σ l , above which there is no spin glass transition. Interestingly, Viet and Kawamura [20] claim that chiral glass ordering persists to slightly larger values of σ. Testing this claim is one of our main motivations for performing simulations at σ = 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, several studies both for the Ising and the Heisenberg SGs suggested that the 1D LR SG model with a power-law exponent σ might show the ordering behavior analogous to the d-dimensional SG model with a SR interaction [23][24][25][26][27][28][29][30][31]. Even a simple empirical formula relating σ and d, d = 2/(2σ − 1), was proposed [23], though the relation is only approximate.…”
Section: Introductionmentioning
confidence: 99%